2020
DOI: 10.1101/2020.05.05.079228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale pathway-specific polygenic risk, transcriptomic community networks and functional inferences in Parkinson disease

Abstract: Polygenic inheritance plays a central role in Parkinson disease (PD). A priority in elucidating PD etiology lies in defining the biological basis of genetic risk. Unraveling how risk leads to disruption will yield disease-modifying therapeutic targets that may be effective. Here, we utilized a high-throughput and hypothesis-free approach to determine biological pathways underlying PD using the largest currently available cohorts of genetic data and gene expression data from International Parkinson's Disease Ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Here, we also found for the first time that patients with higher PRS from PD risk exhibit lower levels of CSF Aβ42, suggesting that similar genes or pathways predispose individuals to an accumulation of Aβ in the brain and to develop PD. This is in agreement with a recent report suggesting that the PD genes from the PRS analysis are enriched for AD genes [2].…”
Section: Discussionsupporting
confidence: 94%
“…Here, we also found for the first time that patients with higher PRS from PD risk exhibit lower levels of CSF Aβ42, suggesting that similar genes or pathways predispose individuals to an accumulation of Aβ in the brain and to develop PD. This is in agreement with a recent report suggesting that the PD genes from the PRS analysis are enriched for AD genes [2].…”
Section: Discussionsupporting
confidence: 94%
“…We have also shown that the neutrophil epigenome is linked less to other SCFAs. A recent study [51] reported that neutrophil degranulation is potentially linked to PD risk. Our gene set enrichment analysis suggests that butyrate-linked epigenetic changes may impact this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…4b). Pathway analysis shows that epigenetic alterations of three recently identified PD polygenic risk pathways [51] (neutrophil degranulation, metabolism of lipids, and innate immune system) in the monocyte and neutrophil epigenome were linked to butyrate levels (Fig. 4c).…”
Section: Epigenetic Links Between Butyrate and Leucocytes Differ Between Cell Typesmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to investigating individual variant effects with colocalization and epistasis, visualizing biological networks can help with understanding complex molecular relationships and interactions. In PD research, genetic and gene expression data has been used in community network analysis to nominate pathways and genes for drug target and functional prioritization 17,18 .…”
Section: Downstream Analyses Of Genetic Variationmentioning
confidence: 99%